Computational study of SENP1 in cancer by novel natural compounds and ZINC database screening - Taghvaei, Somayye; Taghvaei, Alireza; Anvar, Mohammad Saberi; Guo, Chun; Sabouni, Farzaneh; Minuchehr, Zarrin (Frontiers in Pharmacology, 2023)
SENP1 is a protein whose main function is deSUMOylation. SENP1 inhibits apoptosis, increases angiogenesis, estrogen and androgen receptor transcription and c-Jun transcription factor, proliferation, growth, cell migration, and invasion of cancer. The in vivo and in vitro studies also demonstrated which natural compounds especially phytochemicals, minerals, and vitamins prevent cancer. More than 3,000 plant species have been reported in modern medicine. Natural compounds have many anti-cancerous and anti-turmeric properties such as anti-oxidative, antiangiogenic, antiproliferative, and pro-apoptotic properties. In this study, we studied the interaction of natural compounds with SENP1 for its inhibition. We also screened the ZINC database for natural compounds. Molecular docking was performed, the toxicity of compounds was computed, and molecular dynamics simulation (MDS) and essential dynamics (ED) were done for natural compounds with higher free binding energy and the lowest side effects. Moreover, the ZINC database was screened through Libdock and CDOKER, the top twenty compounds were docked to SENP1 and molecular dynamics simulation and essential dynamics were applied for the final three compounds. My research illustrated Resveratrol (of selected compounds) and ZINC85902334 (of ZINC database) constitute a more stable complex than others for SENP1 inhibition. Further clinical trials must be conducted to validate their use as a potential SENP1 inhibitor.